“For better or worse”? A frame analysis of BRICS activities by digital journalists in South Africa - Lungile Augustine, Tshuma (2020)
This paper seeks to examine the discourse on BRICS that are framed by digital journalists in South Africa. South Africa has been going through an uneasy economic path characterised by high unemployment rates, constant power cuts, and their economy relegated into a ‘junk status’. Against this background, BRICS presents a good opportunity for the country to negotiate and address some of its challenges/problems with other economic super-powers within the economic block. This paper comes against a background of silent research on BRICS yet the block has developed into an economic hub which other developing countries benefiting from it for the development of their economies. I therefore argue that South African digital journalists from the country’s leading news websites, News24 and Daily Maverick, are framing BRICS in a manner in which it reflects the socio-economic and political problems affecting the country.  Hence, the study had sought to find out the images of BRICS among the journalist and also information, events, and activities that are being prioritized in reference to South Africa’s challenges. Findings have shown that BRICS is benefiting South Africa. The benefit is seen through trade relations that are framed as having been improved while there are also other potential areas of cooperation that should be utilised.